Diagnosis of water consumption in traditional chinese restaurants / Jennifer Y. Lo, Wilco W. Chan and Kevin Wong - Lo, Jennifer Y.; Chan, Wilco W.; Wong, Kevin (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2010)
decade to become a significant segment of the hospitality sector in the city. Considering all restaurant-types available in the country, Chinese dim sum restaurants have the largest numerical count in Hong Kong. A major concern in the Chinese dim sum restaurant sector over the recent years has been the diverse and harmful forms of pollutants which accompany the food production process. Notably, Chinese restaurants are believed to consume more water and produce more sewage than restaurants serving other cuisines (Deng and Burnett, 2002). This study investigated the water consumption pattern of Chinese dim sum restaurants in a case study. Both qualitative and quantitative data from primary and secondary sources were collected. Results show that the dish washing section used the most amount of water (48%). The factors which affect the extent and nature of water consumption in local dim sum restaurants were also identified It was found that the number of patrons was the chief determining factor with regard to the volume of water consumption in local Chinese restaurants. The gross floor area and operating hours of the restaurant also had an effect on total water consumption. Subsequent to analyzing water use patterns and identifying potential water abuse, some recommendations were made to industry practitioners. By reducing water consumption and sewage generation, the water charge, sewage charge and trade effluent surcharge of a restaurant can be cut down. Restaurant operators can therefore benefit from reduced operating expenses.